Key factors for qualitative realisation of dual career in perspective of the sports - Amantova, I.; Abele, A. (LASE Journal of Sport Science, 2019)
The Murjani Sports Gymasium (MSG) is the only specialized sports education institution in Latvia which provides high school education and simultaneously the realisation of high-performance sports career. Despite the fact that this educational institution has about 400 students/athletes in seven sports, crucial part of the Latvian national teams in these 7 sports contains of the current and graduated students of the MSG. Therefore, the aim of this study is toevaluate the dual career maintenance i.e. situation in Latvia, by particularly assessing the key factors of qualitative dual career realisation. In this matter, based on the literature research the key factors to maintain qualitative dual career were selected. Additionally, the sports leadership evaluated the importance of these factors in dual career realisation. In particularly, five national sport federations' presidents and the Deputy State Secretary-Director of the Sports Department at Ministry of Education and Science of the Republic of Latvia (MES) were asked to evaluate the dual career system in Latvia and to give suggestions for development which has significant meaning in dual career system improvement and development in the Latvian sports industry.The results of the interviews with the sports leadership indicate that all determined key factors proposed by the scientists that influence qualitative dual career realisation play an important role. It could also be surely concluded that dual career maintenance i.e. athletes' support system is in its very early stage of development and the work on the dual career systems' progression must been intensified. Furthermore, based on the research results it would be possible further to develop a more accurate model for the enhancement of the qualitative dual career realizationin Latvia and put forward recommendations for improvement of the dual career structures in Latvia.